Trend and age-period-cohort analysis of colorectal cancer burden attributable to low whole grains intake: a global, regional, and national analysis with predictive modeling (1990–2046) - Wang, Kai; Li, Xiaodan; Guo, Zhiqiang; Chen, Junsheng; Li, Yongsheng; Liu, Hongzhou; Guo, Shuwei (Frontiers in Nutrition, 2025)
BackgroundColorectal cancer (CRC) persists as a major global public health priority, with insufficient whole grain consumption recognized as a clinically significant and modifiable dietary risk factor. However, comprehensive analyses of its spatiotemporal burden and socioeconomic disparities are limited. This study evaluates the global, regional, and national CRC burden attributable to low whole grains intake from 1990 to 2021 and projects trends to 2046.MethodsThis study employed the Global Burden of Disease (GBD) 2021 dataset to quantify the association between low whole grain intake and CRC burden. Analyses were conducted across multiple dimensions: temporal (1990–2021), demographic (stratified by sex and 5-year age intervals), and geographic (categorized by national and regional Socio-demographic Index (SDI) quintiles).ResultsFrom 1990 to 2021, global CRC deaths and disability-adjusted life years (DALYs) attributable to low whole grains intake increased by 82.94% (101,813 to 186,257) and 70.30% (2,540,867 to 4,327,219), respectively. However, age-standardized mortality rates (ASMR) and age-standardized DALYs rates (ASDR) declined globally (AAPC: −0.73 and −0.74). High-SDI regions showed the steepest reductions (ASMR AAPC: −1.17; ASDR AAPC: −1.15), while low-middle-SDI regions experienced rising trends (ASMR AAPC: 0.42; ASDR AAPC: 0.35). Gender disparities persisted: males had higher absolute burdens (2021 deaths: 104,344 vs. 81,912 for females; 2021DALYs: 2527992 vs. 1,799,227), but female ASMR and ASDR declined faster (AAPC: −1.09, −1.12, respectively, vs. −0.47 and −0.47, respectively, for males). Geographically, East Asia, Western Europe, and High-income North America had the highest absolute burdens, whereas Uruguay (ASMR: 5.18/100,000) and Hungary (ASDR: 113.76/100,000) led in age-standardized rates. Cabo Verde exhibited the sharpest increases (ASMR AAPC: 3.16; ASDR AAPC: 2.80). Frontier analysis identified Uruguay and Hungary as high-SDI countries with the largest gaps from efficiency targets. Projections to 2046 suggest continued ASMR/ASDR declines but persistent SDI-driven disparities.ConclusionDespite declining age-standardized rates, absolute CRC burden attributable to low whole grains intake increased due to population growth and aging. Socioeconomic disparities highlight the need for targeted interventions in transitioning regions adopting Western diets. Promoting whole grains consumption and prioritizing high-burden populations could mitigate future CRC burden.